MODEL MULTILITERASI SOSIAL DALAM MEMAKNAI NILAI-NILAI MORALITAS SISWA DI SDN 1 CIKALAHANG - Iis Yeni Sugiarti; Auliya Aenul Hayati (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
THE SOCIAL MULTILITERATION MODEL IN UNDERSTANDING THE VALUES OF STUDENT MORALITIES IN SDN 1 CIKALAHANGLearning that has been done so far only emphasizes the cognitive aspects without introducing the moral values. The social multiliteration learning model in understanding the moral values of students is considered very important because students are required to master an understanding of social phenomena and global demands. Therefore, life skills and careers can be built in students; responsibilities in learning; working and creating; students' ability in civilization; and understand the moral knowledge contained in the learning process. This study aims to describe the needs of learning model and design social multiliteration learning model in understanding the values of morality of students at SDN 1 Cikalahang. The writer uses a case study research with a qualitative approach. Observation and interview used to collect the data. Questionnaire needs and unstructured interviews used as the instruments. Indicators of needs analysis include models, media, competencies and evaluation of learning. Analysis of the needs for learning model obtained a total score of 94 which is very good category, while the design of social multiliteration learning model in interpreting moral responsibility is very necessary because the current morality of students is decreasing. The implementation of social multiliteration learning models can help students in interpreting the moral knowing of responsibility character through the activities of raising rabbits, as well as seen from the effectiveness and attractiveness of student learning interests.